Functionalized Poly(3-hexylthiophene)s via Lithium–Bromine Exchange - Koo, Byungjin (Macromolecules, 2014)
[Image: see text] Poly(3-hexylthiophene) (P3HT) is one of the most extensively investigated conjugated polymers and has been employed as the active material in many devices including field-effect transistors, organic photovoltaics and sensors. As a result, methods to further tune the properties of P3HT are desirable for specific applications. Herein, we report a facile postpolymerization modification strategy to functionalize the 4-position of commercially available P3HT in two simple steps–bromination of the 4-position of P3HT (Br–P3HT) followed by lithium−bromine exchange and quenching with an electrophile. We achieved near quantitative lithium–bromine exchange with Br–P3HT, which requires over 100 thienyl lithiates to be present on a single polymer chain. The lithiated-P3HT is readily combined with functional electrophiles, resulting in P3HT derivatives with ketones, secondary alcohols, trimethylsilyl (TMS) group, fluorine, or an azide at the 4-position. We demonstrated that the azide-modified P3HT could undergo Cu-catalyzed or Cu-free click chemistry, significantly expanding the complexity of the structures that can be appended to P3HT using this method.